Proper flying capacitor selection for performance enhancement of five-level hybrid active neutral-point-clamped inverters - Hakami, Samer Saleh; Lee, Kyo Beum (Journal of Power Electronics, 2022)
Flying capacitors (FCs) are very important in multilevel inverter systems when it comes to synthesizing additional voltage levels for various medium-voltage industrial applications, including renewable energy, motor drives, and power transmission. In particular, they are responsible for forming the five-level output pole voltages in five-level hybrid active neutral-point-clamped (ANPC) topologies. This is only possible when the FCs reach their reference values (i.e., 25% of the DC-link value). When a five-level hybrid ANPC inverter operates in the high-frequency (HF) range, the output three-phase current waveforms are less distorted when compared to the low-frequency (LF) performance. Instantaneously achieving a five-level output pole voltage during HF operation is a challenging task. This is due to the large capacitance of some existing types of FCs. In this study, a novel analysis of the effects of a FC on the performance of a five-level hybrid ANPC inverter is presented with simulation and experimental validations. Film capacitors significantly enhanced system performance when compared to electrolytic capacitors due to their many advantageous features, including the ability to charge and discharge quickly during HF operation. In addition, the total harmonic distortion of the output pole voltage is significantly suppressed. Consequently, the size of the required filter can be reduced. Therefore, the proposed system is highly desirable for various industrial applications.
Keywords: Active neutral point clamped; Five-level hybrid active neutral-point-clamped inverte; Flying capacitor; High frequency operation; Multi Level Inverter (MLI); Multilevel inverter; Multilevels; Neutral-point clamped inverters; Performance enhancements; Pole voltages; Five-level hybrid ANPC inverter; Flying capacitor; HF operation; Multilevel inverters